Interdisciplinary Treatment of Endo-Perio Lesion of Mandibular Molar Accompanied with Vertucci Type II: A Case Report - Radita, Andi R.; Nugroho, Juni J. (Journal of Case Reports in Dental Medicine, 2025)
Introduction: Endo-periodontal lesions are characterized as bacterial infection conditions that cause widespread periodontal tissue destruction and inflammation or pulp necrosis conditions. These lesions occur simultaneously in the periodontal and periapical tissues of a single tooth. Treatment of these lesions requires a multidisciplinary approach that integrates endodontic and periodontal therapy. Knowledge of the pulp and periodontal relationship, the complexity of the root canal system is essential in the management of these cases. The use of periapical radiographs and CBCT are crucial for the success of this treatment.Case:  A second mandibular right molar was diagnosed as a primary endodontic with secondary periodontal lesion, and treated with a combination of endodontic and periodontal therapy. Tooth 47 with Vertucci type II root canal configuration was subjected to multi-visit endodontic treatment, beginning with placement of root canal dressings between visits and final composite resin restoration. Subsequent procedure with scaling, root planning and curettage from Periodontics department. A post-treatment control showed good results.Discussion: Endo-perio lesions are clinical conditions that involve inflammatory conditions in the pulp and periodontal tissues simultaneously. This relationship can occur through anatomical pathways such as the apical foramen and lateral canals, as well as non-physiological pathways due to trauma or improper procedures. Treatment of these lesions requires a multidisciplinary approach to achieve optimal results.Conclusion: The treatment of endo-perio lesions accompanied by Vertucci type II in molar teeth can be completed well, because the dentist is able to perform the examination appropriately and involve multidisciplinary treatment.